The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1530/eje-13-0263
|View full text |Cite
|
Sign up to set email alerts
|

EJE Prize 2013: Regulation of aldosterone secretion: from physiology to disease

Abstract: Arterial hypertension is a major cardiovascular risk factor that affects between 10 and 40% of the population in industrialized countries. Primary aldosteronism (PA) is the most common form of secondary hypertension with an estimated prevalence of around 10% in referral centers and 4% in a primary care setting. Despite its high prevalence until recently, the underlying genetic and molecular basis of this common disease had remained largely obscure. Over the past decade, a number of insights have been achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 88 publications
0
30
0
5
Order By: Relevance
“…In addition, in some studies higher aldosterone and lower potassium levels at diagnosis have been described and larger tumours were found compared with non-mutated cases (37,38,39,40,41). Conversely, in some but not all studies, it has been shown that patients harbouring ATPase mutations are more commonly men and are associated with the most severe forms of PA and rather smaller size tumours (30,39). These findings are particularly relevant in the familial form of PA (FH type 3) where specific mutations in the KJNC5 gene, as those altering the G151E amino acid, are associated with mild aldosteronism compared with those with G151R mutation that have a more severe clinical phenotype (28,32).…”
Section: Genetic Determinants Of Pamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in some studies higher aldosterone and lower potassium levels at diagnosis have been described and larger tumours were found compared with non-mutated cases (37,38,39,40,41). Conversely, in some but not all studies, it has been shown that patients harbouring ATPase mutations are more commonly men and are associated with the most severe forms of PA and rather smaller size tumours (30,39). These findings are particularly relevant in the familial form of PA (FH type 3) where specific mutations in the KJNC5 gene, as those altering the G151E amino acid, are associated with mild aldosteronism compared with those with G151R mutation that have a more severe clinical phenotype (28,32).…”
Section: Genetic Determinants Of Pamentioning
confidence: 99%
“…This form of PA results from an unequal crossing over between the highly homologous CYP11B2 and CYP11B1 genes that code for aldosterone synthase and steroid 11b-hydroxylase, producing a chimeric gene that is under adrenocorticotrophin (ACTH) rather than RAS control (28,29,30).…”
Section: Genetic Determinants Of Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Based on several basic investigations the intra-adrenal RAS, which is a major regulator of aldosterone generation, was extensively focused on in investigating the mechanism of excessive aldosterone secretion. 9,10 To date, the pathophysiological role of the RAS in PA has been elucidated and components of the RAS such as AGTR1, AGTR2, CYP11B1, CYP11B2 and mineralocorticoid receptor have been reported to be widely involved in the regulation of autonomous aldosterone. It is known that the activation of AGTR1 can trigger the synthesis and secretion of aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone is synthesised in the zona glomerulosa of the adrenal gland under the regulation of the renin-angiotensin system (RAS), extracellular potassium levels and adrenocorticotropic hormone (ACTH). Its function in regulating salt and fluid balance is achieved by altering the sodium transport machinery of renal tubular epithelial cells (Loffing & Korbmacher 2009) and is critical for protection against hypovolaemia (Fine et al 1958, Beuschlein 2013.…”
Section: Pre-receptor and Receptor Mechanisms Determining Ligand-specmentioning
confidence: 99%